Encouraging cartilage production - Stadler, H Scott (eLife, 2020)
A long non-coding RNA called GRASLND is essential to help stem cells create stable cartilage.
Keywords: mesenchymal stem cells; tissue engineering; regenerative medicine; rnf144a-as1; stem cells